A5RE4X[TO4]4 crystal growth and photoluminescence. Hydroflux synthesis of sodium rare earth silicate hydroxides1. Issue 25 (7th July 2015) - Latshaw, Allison M.; Chance, W. Michael; Trenor, Nathan; Morrison, Gregory; Smith, Mark D.; Yeon, Jeongho; Williams, Derek E.; zur Loye, Hans-Conrad
<x xml:space="preserve">Abstract</x> Single crystals of Na5RE4(OH)[SiO4]4 (RE = Pr, Nd, Sm, Eu, Tb–Yb, Y) were grown using the hydroflux synthetic method. Photoluminescence properties and magnetic susceptibility were measured.